Metastatic Squamous Cell Carcinoma to the Cervical Lymph Nodes From an Unknown Primary Cancer: Management in the HPV Era - Civantos, Francisco J.; Vermorken, Jan B.; Shah, Jatin P.; Rinaldo, Alessandra; Suárez, Carlos; Kowalski, Luiz P.; Rodrigo, Juan P.; Olsen, Kerry; Strojan, Primoz; Mäkitie, Antti A.; Takes, Robert P.; de Bree, Remco; et al. (Frontiers in Oncology, 2020)
BACKGROUND Patients with metastases in the lymph nodes of the neck and no obvious primary tumor- neck cancer with unknown primary (NCUP) represent a management challenge. A majority of patients have metastatic squamous cell carcinoma (SCC), although other histologies do occur. METHODS We comprehensively reviewed the literature, compared available guidelines, and conferred with an international team of experts. RESULTS Positron Emission Tomography - Computed Tomography (PET-CT) and fine needle aspiration (FNA) under ultrasound guidance increase accuracy of diagnosis. Immunohistochemistry (IHC), determination of Human Papilloma Virus (HPV) status, by p16 staining or by in situ hybridization (ISH), and next-generation gene sequencing can guide us regarding probable primary sites and tumor biology. Narrow Band Imaging (NBI) has been introduced for the early detection of subtle mucosal lesions. Direct Laryngoscopy (DL) and tonsillectomy have long been procedures used in the search for a primary site. More recently, TransOral Robotic Surgery (TORS) or Transoral LASER Microsurgery (TLM) have been introduced for lingual tonsillectomy. CONCLUSIONS New technologies have been developed which can better detect, diagnose, and treat occult primary tumors. Decisions regarding therapy are based on the primary tumor site (if discovered) and N stage. Options include neck dissection with or without postoperative adjuvant therapy, primary irradiation, or combined chemotherapy with irradiation. The preferred treatment of patients whose primary remains unidentified is controversial.